Effects of Pre-Incubation Storage on the Hatchability of Quail (Coturnix coturnix japonica) Eggs in the Sahel Region of Nigeria - Usman, B.A.; Mani, A.U.; Garndawa, I.I. (International Journal of Poultry Science, 2008)
A study to determine the effect of pre-incubation storage of the eggs of the Japanese quail (Coturnix coturnix japonica) was conducted during the cool harmattan season in the north-east arid region (Sahel) of Nigeria. Eggs were collected daily from six-months-old quail and stored at room temperature (25-29 °C) for 0 to 20 days before incubation in an electric incubator. Eggs that failed to hatch were opened for determination of fertility and estimation of time of death of embryos. A total of 196 (29.3 %) eggs out of 668 incubated hatched successfully. The length of pre-incubation storage was negatively correlated (r = -0.91; P < 0.0001) with hatchability. The highest hatchability (72.3%) was obtained from eggs that were not stored (Day 0 of storage). Hatchability dropped sharply after storage for 9 days. No egg hatched following pre-incubation storage of over 11 days. Among the unhatched eggs, there were significantly more apparently infertile than fertile eggs (P < 0.0002). There was no relationship between pre-incubation length of storage and the proportion of embryos that died in early, middle or late incubation period. However, the proportion of the apparently infertile eggs increased with increasing length of pre-incubation storage (r = 0.95; P < 0.0001). No egg stored for 18 days or more was found to be apparently fertile. It was concluded that the length of pre-incubation storage has detrimental effect on hatchability of quail eggs in the Sahel area and that quail eggs for incubation should not be stored at room temperature for more than 9 days, even in the coolest season.